Does small-scale irrigation affect women’s time allocation? Insights from Ethiopia - Lee, Yeyoung; Bryan, Elizabeth; Mason, Nicole M.; Hassen, Ibrahim Worku; Theriault, Veronique; Ringler, Claudia (Elsevier, 2025)
Small-scale irrigation (SSI) interventions have received increasing attention as a potential pathway for women’s empowerment in sub-Saharan Africa. One key aspect of women’s empowerment that SSI can influence is women’s time burden. Hypothesized benefits of SSI for women are less energy exertion and reduced labor in agriculture. Yet, these hypotheses have not been tested empirically. We explore how household adoption of different SSI technologies affects the time allocation of women in the household, using two rounds of intrahousehold panel survey data from Ethiopia. Two different approaches are used to address potential endogeneity issues related to time-constant and time-varying factors that may be correlated with both SSI and time use: an instrumental variables-correlated random effects approach and a fractional multinomial logit-correlated random effects with control function approach. The results suggest that household use of SSI in general is associated with an increase in women’s leisure time. The results further suggest that household use of motor pumps is associated with an increase in women’s leisure time and reductions in the time they spend on farming and personal care. Given that women often provide the labor for irrigation using manual, labor-intensive methods, such as watering cans, buckets, or hand- or foot-powered treadle pumps, the results suggest that SSI using motorized methods has the potential to free up women’s time in farming and enable more leisure time. These findings have broad implications for women’s empowerment and labor allocation. Future research using new and more comprehensive data could explore the mechanisms for the findings in this study and determine if SSI enables women to improve their ability to allocate their time to activities they prefer.